KONSEP PENDIDIKAN KARAKTER ISLAM MENURUT IBNU MASKAWAIH DAN IMPLIKASINYA BAGI PENDIDIKAN KARAKTER DI INDONESIA - Abidin, Zainal (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2014)
Character is a crucial problem in Islam, and the character of education must be applied for all of Moslems in the world because in the Islamic perspective a branch of the pilars and fundamental doctrine of Islam is developing akhlak (noble character) beside aqidah, and syariah. Ibnu Maskawaih is the intelectual muslimÂ and he is who have the doctrine of golden mean. He introduced in Islam about and improved how to be the good moslem, and he was thinking that caharacter education will be given to the human being since early age, because it is a integrated system in Islamic religion and will be identity of Islamic society. Good character must be possessed for every one to make the harmony in the entire of their life. Islam as the religion was supported to developed for akhlak al-Mahmudah because the prophet Muhammad have the mission the recontruction for good character in the world especially for all of Moslems.Keywords: The Character Education of Maskawaih